Search for Vigna species conferring resistance to Mungbean yellow mosaic virus in mungbean. Issue 2 (15th August 2014) - Sudha, M.; Karthikeyan, A.; Shobhana, V. G.; Nagarajan, P.; Raveendran, M.; Senthil, N.; Pandiyan, M.; Angappan, K.; Balasubramanian, P.; Rabindran, R.; Bharathi, M.
Abstract : Mungbean yellow mosaic virus (MYMV) is a disastrous pathogen of mungbean. It is widespread in most of southern India and no complete resistance has been identified among its commercial cultivars. Two isolates of MYMV, representing its diversity, were used to assess and characterize the susceptibility reaction of all the three species of Vigna . The seeds were agroinoculated with the virus and the presence of the viral DNA was confirmed after 12 d by reverse transcriptase-polymerase chain reaction (RT-PCR) analysis after which the plants were monitored for the expression of symptoms. All of the 20 accessions of Vigna radiata and ten accessions of Vigna mungo were systemically infected with MYMV, and they all produced typical symptoms. On the other hand, the 24 accessions of Vigna umbellata were found to be resistant to both the isolates. For additional affirmation, three representative accessions of V . radiata and V . mungo and all the accessions of V . umbellata were agroinoculated, and quantitative RT-PCR was performed for the quantitative detection of the MYMV. The mRNA transcripts of MYMV were detected in V . radiata and V . mungo plants but not in the V . umbellata plants. Researching the molecular basis of the resistance in V. umbellate against MYMV might definitely be very constructive for developing resistant varieties of mungbean on a commercial scale. This genetic quality offering resistance to MYMV could also be incorporated into V . radiata / V . mungo by means of interspecific crosses.